ROCKETING SHEEP: AFFECTIVE DISCIPLINE IN ANONYMOUS MOBILE SOCIAL MEDIA JODEL DURING THE COVID-19 PANDEMIC - Laaksonen, Salla-Maaria; Rantasila, Anna (AoIR Selected Papers of Internet Research, 2021)
The Covid-19 pandemic has sparked online discussion in unprecedented volumes, as citizens use social media to share their opinions and concerns regarding the prevention measures, for instance. Much of such activity takes place under real names on popular platforms such as Facebook and Twitter. However, parallel to these platforms more anonymous spaces remain and flourish, including completely anonymous services such as Secret.ly and Ask.fm, or pseudonymized services such as Reddit. This study focuses on Covid-19 related discussion on mobile social media platform Jodel, an anonymous-by-design social media application that allows messaging users who are geographically close. In this paper, we explore discussions about the Covid-19 pandemic on Jodel in Helsinki, Finland, through the theoretical notion of affective discipline. Our data is collected during a virtual, mobile ethnography that followed the discussions on the #corona channel in Jodel in Helsinki during 2020-21. We argue that the anonymity of Jodel provided its users a space to discuss the restrictive measures in a more relaxed manner than real-name-based social media. This also endows the conversations with deeper and different affective attunement than what public discussion would. While the discussions contain moral judgments, they were also rife with humor, irony and distanced spectatorship of the ongoing pandemic, resonating with the carnivalistic discussion cultures of other anonymous and pseudonymous platforms. We argue that anonymous and ephemeral platforms like Jodel, where identities and histories are nonexistent, bring out the affective dynamics of online discussions, and the related forces that assemble and disassemble communities.